Zur Wirkungskraft der politischen Karikatur im Werk von Thomas Nast - Jakosz, Mariusz (Acta Neophilologica, 2025)
With the edited volume Thomas Nast. Karikaturist zwischen Kunst und Kritik, an interdisciplinary publication is presented for the first time in the German-speaking world that offers a comprehensive examination of the work of German-American caricaturist Thomas Nast (1840–1902) from cultural-historical, political-scientific, and visual-rhetorical perspectives. Nast was not only a virtuoso illustrator but also an active participant in the political discourse of the 19th century. His caricatures played a significant role in shaping public opinion: they not only reflected contemporary political developments but also actively influenced them. His campaigns against the corruption of Tammany Hall and his firm stance during the American Civil War are still regarded as exemplary illustrations of the political potential of caricature. The collected contributions explore the life, work, and legacy of Thomas Nast, offering a multifaceted and nuanced portrait of an artist whose influence on the political iconography of the United States extends to the present day, while also leaving behind a body of work marked by ideological tensions and ambivalences